Odpowiedzi

2010-04-01T15:26:19+02:00
A) y+y = 9 + 3
2y=12 | ; 2
y = 6
b)1/2 z - z + -1 - 6
0,5 z = -7 | ; o 5
z + 3, 5

2010-04-01T15:39:14+02:00
A) y - 3 = 9 - y
y+y=9+3
2y=12 /:2
y=6

b) 1/2z + 6 = z - 1

c) 1/7x = -2
d) 5y = 13 /:5
y=2.6
e) -3/4z = 3/4
f) -6u = 1/3
g) y*12 = -60
12y=-60
y=-5
h) -2w = -1/2
i) 5a = 0 /:5
a=0
j) -7b = 7/8
k) 22(-c) = -66
2010-04-01T15:52:28+02:00

a) y - 3 = 9 - y
y + y = 9 + 3
2y = 12 /: 2
y = 6

b) 1/2z + 6 = z - 1
1/2z - z = -1 - 6
-1/2z = -7 /: (-1/2)
z = 7/2
z = 3 i 1/2

c) 1/7x = -2 /: 1/7
x = -2 x 7
x = -14

d) 5y = 13 /: 5
y = 13/5
y = 2 i 3/5

e) -3/4z = 3/4 /: (-3/4)
z = -1

f) -6u = 1/3 /: (-6)
u = 1/3 x (-1/6)
x = -1/18

g) y*12 = -60 /: 12
y = -5

h) -2w = -1/2 /: (-2)
w = (-1/2) x (-1/2)
w = 1/4

i) 5a = 0 /: 5
a = 0

j) -7b = 7/8 /: (-7)
b = 7/8 x (-1/7)
b = -7/56
b = -1/8

k) 22(-c) = -66
-22c = -66 /: (-22)
c = 3